The impact of agricultural knowledge transfer resources on farm level profitability during the economic recession – a quantitative study. Issue 2 (15th March 2019) - Cawley, A.; O'Donoghue, C.; Heanue, K.; Hilliard, R.; Sheehan, M.
ABSTRACT: Purpose: The impact of agricultural knowledge transfer (KT) is related to the access to and the quality of services available. Within this context, the allocation of resources in terms of KT offices and the number of advisers are important considerations for understanding KT impact. This quantitative study evaluates the impact of KT resources on farm profitability for clients in Ireland during the recessionary period 2008–2014. Design/Methodology: Teagasc, the public KT service provider in Ireland, experienced significant office closures (43%) and a reduction in advisers (38%) during the economic crisis, yet client numbers declined only slightly (4.5%). Administrative data are merged with a panel data set on farm-level performance to evaluate the impact through Random Effects estimation. Findings: The results show that clients gained a 12.3% benefit to their margin per hectare over the period. However, there was a negative effect of 0.2% for each additional client assigned to the adviser which averaged at 9.6%. Practical Implications: The quantitative findings provide a measure of impact that represents the value for money for the KT service. The key implication is that the client ratio for advisers should be considered when allocating resources and lower ratios would positively impact client margins. Theoretical Implications: This article outlines the value of quantitative studies to estimate impact in a clear translatable manner which can aid the policy discussion around resource deployment. Originality/Value: This study evaluates the impact of KT during a recessionary period when resources were constrained, and uses client ratios to examine the spatial effects.